Risk factors for musculoskeletal injury in elite pre-professional modern dancers: A prospective cohort prognostic study - Bronner, S.; Bauer, N. N. (Physical Therapy in Sport, 2018)
Objectives: To examine risk factors for injury in pre-professional modern dancers. Design: With prospectively designed screening and injury surveillance, we evaluated four risk factors as categorical predictors of injury: i) hypermobility; ii) dance technique motor-control; iii) muscle tightness; iv) previous injury. Screening and injury data of 180 students enrolled in a university modern dance program were reviewed over 4-yrs of training. Dancers were divided into 3-groups based on predictor scores. Dance exposure was based on hours of technique classes/wk. Negative binomial log-linear analyses were conducted with the four predictors, p<0.05. Results: Dancers with low and high Beighton scores were 1.43 and 1.22 times more likely to sustain injury than dancers with mid-range scores (p=0.03). Dancers with better technique (low or medium scores) were 0.86 and 0.63 times less likely to sustain injury (p=0.013 and p<0.001) compared to those with poor technique. Dancers with one or 2-4 tight muscles were 2.7 and 4.0 times more likely to sustain injury (p=0.046). Dancers who sustained 2-4 injuries in the previous year were 1.38 times more likely to sustain subsequent injury (p<0.001). Conclusions: This contributes new information on the value of preseason screening. Dancers with these risk factors may benefit from prevention programs.